Crater view the Taal Volcano Learning Hub - Cantong, Keneth Christian A.; Bo-ot, Luis Ma. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The Taal Volcano Learning Hub acts as a support facility for ecotourism in the lakeshore town of Talisay, Batangas by providing a venue focused on educating visitors on volcanology and geology, as well as on disaster risk reduction management and sustainable tourism practices. It integrates an interactive volcano museum, volcano monitoring facilities, a community livelihood center, and various accessible open spaces, such as an amphitheater and esplanade. Furthermore, it acts as a jump-off point for educational ecotourists going to the volcano island.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Ecotourism -- Batangas -- Philippines